Mariel of Redwall - Jacques, Brian (Jacques, Brian. Redwall series, 2003)
The mousemaid Mariel achieves victory at sea for the animals of Redwall Abbey, fighting the savage pirate rat Gabool the Wild, warlord of rodent corsairs.